2024
DOI: 10.1111/gcb.17139
|View full text |Cite
|
Sign up to set email alerts
|

Persistent net release of carbon dioxide and methane from an Alaskan lowland boreal peatland complex

Eugénie S. Euskirchen,
Colin W. Edgar,
Evan S. Kane
et al.

Abstract: Permafrost degradation in peatlands is altering vegetation and soil properties and impacting net carbon storage. We studied four adjacent sites in Alaska with varied permafrost regimes, including a black spruce forest on a peat plateau with permafrost, two collapse scar bogs of different ages formed following thermokarst, and a rich fen without permafrost. Measurements included year‐round eddy covariance estimates of net carbon dioxide (CO2), mid‐April to October methane (CH4) emissions, and environmental vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
2

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 170 publications
2
6
2
Order By: Relevance
“…Due to decreasing air temperatures late in the growing season and the high thermal diffusivity of saturated peat (Arkhangelskaya & Gvozdkova, 2019), soil temperature at 5 cm in the wetter young bog decrease earlier S1) e.g., potentially accounting for greater cumulative mature bog GPP. While the mature bog had higher cumulative GPP, the range of annual GPP observed across the thermokarst bog stages (−105 to −383 g C-CO 2 m −2 year −1 ) was lower than previously reported annual GPP estimates from thermokarst bogs in Alaska (−569 to −574 g C-CO 2 m −2 year −1 ; Euskirchen et al, 2024), and wetlands across the boreal region (−406 g C-CO 2 m −2 year −1 ; Virkkala et al, 2021). Our lower annual estimates of GPP in the young and intermediate bogs may be due to surface inundation conditions present at our site, which were rarely found in Alaskan thermokarst sites (Euskirchen et al, 2024).…”
Section: Our Results Show That Interannual Variability In Water Tablecontrasting
confidence: 66%
“…Due to decreasing air temperatures late in the growing season and the high thermal diffusivity of saturated peat (Arkhangelskaya & Gvozdkova, 2019), soil temperature at 5 cm in the wetter young bog decrease earlier S1) e.g., potentially accounting for greater cumulative mature bog GPP. While the mature bog had higher cumulative GPP, the range of annual GPP observed across the thermokarst bog stages (−105 to −383 g C-CO 2 m −2 year −1 ) was lower than previously reported annual GPP estimates from thermokarst bogs in Alaska (−569 to −574 g C-CO 2 m −2 year −1 ; Euskirchen et al, 2024), and wetlands across the boreal region (−406 g C-CO 2 m −2 year −1 ; Virkkala et al, 2021). Our lower annual estimates of GPP in the young and intermediate bogs may be due to surface inundation conditions present at our site, which were rarely found in Alaskan thermokarst sites (Euskirchen et al, 2024).…”
Section: Our Results Show That Interannual Variability In Water Tablecontrasting
confidence: 66%
“…Gaps in winter SMAP data were filled with zero values to represent frozen soils for upscaling. Soil moisture has been identified as one of the important, controlling factors of freshwater wetland CH4 fluxes (Euskirchen et al, 2024;Voigt et al, 2023). Passive microwave radiometermeasured brightness temperature was merged with estimates from the GEOS Catchment Land Surface and Microwave Radiative Transfer Model in a soil moisture data assimilation system, to generate global products of surface and rootzone soil moisture (Reichle et al, 2017).…”
Section: Reanalysis Data and Satellite Data Productsmentioning
confidence: 99%
“…Sites in Alaska, fitting these criteria, were found through the ABCFlux database (Virkkala et al 2021) shown in Figure 1. The pair of moist and wet sites in discontinuous permafrost belong to the Alaskan Peatland EXperiment (Turetsky et al 2023;Euskirchen et al 2024)…”
Section: Field Sitesmentioning
confidence: 99%